Polska reforma gospodarcza po czterech latach a kryteria oceny systemów ekonomicznych - Wilczyński, Wacław (Wydział Prawa i Administracji UAM, 1986)
After the four years in the sate of implementation off the reform is insuffiicieint. New mechanisms of the economic system are still not working. The anticipated economic revival has not occlrred. Poor progress of the reform is effected mostly by the subjective factors, particularly by the insufficient reconstruction of the regulating sphere of the economy. Central economic organs as well as their real functions have not been considerably transformed. There is a tendency observed to reinterpret the reform into the instrumental direction, limiting transformation of economic relations. The lack of qualitative breakthrough in the economic system is clearly visible in the sphere of money and market relations. In the result of continuing traditional pricing policies and the so-called soft financing of wages, the producer market prevails. At the same time no situation is created to create a surplus of effect over expenditures. A clear articulation of the reform targets and a consequent and stable policy of transforming economic relations and bringing into operation mechanisms of economic constraint are necessary to assure the success to the reform. It calls for transforming the State from the director into the sovereign of the national economy and departing from identifying state-controlled economy with the economy of centralistic system of managment.
The Polish economic reform after four years and the criteria of evaluation of the economic systems